The Role of Islamic Mass Organizations in The History of The Development of Islam in South Sulawesi Before Independence (1913-1945) - Khaeruddin, Khaeruddin (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This article discusses the role of Islamic Community Organizations in the history of the development of Islam in South Sulawesi from 1905-1998. The writing method used is the historical method which includes Heuristics, Criticism, Interpretation, and Historiography. Islamic Community Organizations (Ormas) were triggered by the drive due to the growth of patriotic and nationalistic behaviour which at the same time became a response to the problems that occurred among the Indonesian people at the end of the 19th century. The development of Islamic Community Organizations in South Sulawesi has had a positive impact based on historical facts starting from trade contacts to the spread of Islam in South Sulawesi in 1605 during the reign of King Tallo, namely Sultan Alauddin. Organizations based on Islamic values that exist in Indonesia, especially in South Sulawesi, historically consist of Sarekat Islam, Nadhatul Ulama, and Muhammadiyah.